Pact for national literacy at the right age (pnaic) and the pedagogical practice of literacy teachers in the field education: possible contributions - Silva, Luza nira de Deus Pereira da Silva; Souza, Regina Aparecida Marques de Souza (Revista Hipótese, 2018)
This article is part of the ongoing research project and consists of an analytical study of the possible contributions of the PNAIC to the improvement of the work of the literacy teacher inserted in the context of the field in view of the child as subject of law. The research has a qualitative approach, bibliographical, documentary and semistructured interviews. For analysis of the results, we rely on the assumptions of the Cultural Historical theory for a better understanding of the processes of appropriation of the written culture. As for the education of the field, we have recourse to the authors of the field to articulate questions related to the written culture and the context of the field. Preliminary results have demonstrated the demand for a policy that addresses the education of the countryside in its different realities. It is concluded that public policies must be present and assumed by all, so that the literacy of rural children is consolidated.